2012
DOI: 10.2224/sbp.2012.40.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Social Axioms and Implicit Attitudes About People with Disabilities

Abstract: We investigated the relationship between social axioms and implicit attitudes toward people with disabilities. Participants were 101 undergraduate students (male = 30, female = 71) from a university in Beijing. Social axioms were assessed using the Social Axioms Survey (Leung et al., 2002) and implicit attitudes were measured using the Implicit Association Test (Greenwald, McGhee, & Schwartz, 1998). Data analysis showed that the social axiom dimension of fate control was negatively related to implicit attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…While meta-analysis confirmed significant moderate preference for nondisabled individuals, there may be differences between sample groups, as suggested by significant heterogeneity. For example, the two studies reporting the highest D -scores (Chen et al, 2011; Ma et al, 2012) were both conducted with Chinese participants, suggesting possible cultural influences on implicit attitudes. Differences in implicit bias between cultural groups were also suggested by findings of studies that investigated racial differences (Coleman et al, 2015; Friedman, 2019; Harder et al, 2019; Jiang et al, 2021; Thomas et al, 2014; VanPuymbrouck et al, 2020); however, such studies compared racial groups within a specified country rather than between countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While meta-analysis confirmed significant moderate preference for nondisabled individuals, there may be differences between sample groups, as suggested by significant heterogeneity. For example, the two studies reporting the highest D -scores (Chen et al, 2011; Ma et al, 2012) were both conducted with Chinese participants, suggesting possible cultural influences on implicit attitudes. Differences in implicit bias between cultural groups were also suggested by findings of studies that investigated racial differences (Coleman et al, 2015; Friedman, 2019; Harder et al, 2019; Jiang et al, 2021; Thomas et al, 2014; VanPuymbrouck et al, 2020); however, such studies compared racial groups within a specified country rather than between countries.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies found no significant difference in implicit bias between sexes, when differences were found, they trended similarly in that males reported greater implicit bias to PWD (Chen et al, 2011; Clément-Guillotin et al, 2018; Levine et al, 2021; Thomas et al, 2014; VanPuymbrouck et al, 2020). There was also a lack of reliability in reporting results on sex differences, with some studies reporting no differences between sexes not reporting their analyses (Ma et al, 2012; Murch et al, 2018). Similarly, in studies investigating age and implicit bias, results were mixed, some finding older adults to have greater implicit bias (Friedman, 2019; VanPuymbrouck et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social axioms have been shown to predict attitudes and behaviors such as psychological well-being, locus of hope, coping and adjustment, growth mindset, dyadic adjustment, and post traumatic growth (Bernardo, 2013; Bernardo et al, 2021; Bernardo & Nalipay, 2016; Chen et al, 2016; Iliescu et al, 2017; Joshanloo et al, 2010; Lai et al, 2007). Nalipay et al (2017), views of the self (Chen et al, 2016), attitudes about people with disabilities (Ma et al, 2012), and personality factors (Chen et al, 2006; Leung, Lam et al, 2012).…”
Section: Social Axiomsmentioning
confidence: 99%
“…With reference to the domain of social psychology ; these studies found that fate control was inversely associated with implicit attitudes (Ma et al, 2012); self-effacement was significantly predicted by reward for application whereas enhancement of others and avoiding attention was significantly predicted by social cynicism ,the relationships of perceived causes to remedies were greater than those of social axioms and values (Chen & Bond, 2012); for the values of self-direction, absolute reciprocity had been shown with the absence of contemporary associations between values and beliefs (Goodwin et al, 2012); and workfamily conflict was found to be a significant forerunner of distress, but it put forth little influence on social cynicism . Furthermore, reward for application and social cynicism was positively and social complexity was negatively associated to hierarchic self-interest i.e., personal value preferences (Dragolov & Boehnke, 2015) ,self-views as a proximal force and world views as a distal force appeared to matter in subjective evaluation of people's lives (Chen et al, 2016); social axioms significantly predicted modest behavior (Chen et al, 2017) , religiosity, reward for application, and fate control were related to dyadic adjustment (Iliescu et al, 2017); and relation between need frustration and social cynicism was moderated by implicit affiliation-intimacy motive (Hofer et al, 2017).…”
Section: Research Trends In the Second Decade (From 2012 To Date)mentioning
confidence: 99%